2018
DOI: 10.1016/j.chest.2018.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Expiratory Flow Limitation During Mechanical Ventilation

Abstract: Expiratory flow limitation (EFL) is present when the flow cannot rise despite an increase in the expiratory driving pressure. The mechanisms of EFL are debated but are believed to be related to the collapsibility of small airways. In patients who are mechanically ventilated, EFL can exist during tidal ventilation, representing an extreme situation in which lung volume cannot decrease, regardless of the expiratory driving forces. It is a key factor for the generation of auto- or intrinsic positive end-expirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 81 publications
1
55
0
1
Order By: Relevance
“…This is consistent with the hypothesized cause for airway collapse in spontaneously breathing patients with active expiration, highlighting the close relationship between this condition and the wider concept of expiratory flow limitation. 3,28 Importantly, in our patients with airway closure, the increase in the expiratory driving pressure (i.e., plateau pressure minus set PEEP) produced by pneumoperitoneum did not result in reduction in end-expiratory lung volume, which is itself a diagnostic criterion for certifying limited expiratory flow. 3 Other authors reported respiratory mechanics compatible with airway closure during laparoscopic surgery in obese patients, showing that neither the "critical pressure" (i.e., the airway opening pressure) nor end-expiratory esophageal pressure was modified by surgical pneumoperitoneum and suggesting that this procedure could not act as a compression force for lungs and airways at end expiration.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is consistent with the hypothesized cause for airway collapse in spontaneously breathing patients with active expiration, highlighting the close relationship between this condition and the wider concept of expiratory flow limitation. 3,28 Importantly, in our patients with airway closure, the increase in the expiratory driving pressure (i.e., plateau pressure minus set PEEP) produced by pneumoperitoneum did not result in reduction in end-expiratory lung volume, which is itself a diagnostic criterion for certifying limited expiratory flow. 3 Other authors reported respiratory mechanics compatible with airway closure during laparoscopic surgery in obese patients, showing that neither the "critical pressure" (i.e., the airway opening pressure) nor end-expiratory esophageal pressure was modified by surgical pneumoperitoneum and suggesting that this procedure could not act as a compression force for lungs and airways at end expiration.…”
Section: Discussionmentioning
confidence: 63%
“…3,28 Importantly, in our patients with airway closure, the increase in the expiratory driving pressure (i.e., plateau pressure minus set PEEP) produced by pneumoperitoneum did not result in reduction in end-expiratory lung volume, which is itself a diagnostic criterion for certifying limited expiratory flow. 3 Other authors reported respiratory mechanics compatible with airway closure during laparoscopic surgery in obese patients, showing that neither the "critical pressure" (i.e., the airway opening pressure) nor end-expiratory esophageal pressure was modified by surgical pneumoperitoneum and suggesting that this procedure could not act as a compression force for lungs and airways at end expiration. 6,7 Differently, our findings indicate that pneumoperitoneum increases esophageal pressure and airway opening pressure: in previous case series, 6,7 patients were studied in the supine or reverse Trendelenburg position, while our study shows pneumoperitoneum effects in head-down position.…”
Section: Discussionmentioning
confidence: 63%
“…12 However, patients with unstable airways or reduced lung volumes may be susceptible to expiratory flow limitation during compressive or forced expiratory maneuvers, which is believed to be related to the collapsibility of airways. 28,29 If the airways collapse, the downstream flow drops to zero and secretion removal is interrupted. 12,28 In mechanically ventilated patients, expiratory flow limitation is frequently observed in individuals with COPD, obesity, and cardiac failure, and this limitation is influenced by fluid status, the patient's position, bronchoconstriction, and ventilatory conditions.…”
Section: Airways Dynamic Compressionmentioning
confidence: 99%
“…Moreover, improved modelling, for example adding EIT signals, may improve alignment between the ventilator and the patient by modelling patient efforts. Expiratory flow limitation (EFL) is believed to occur when smaller airways constrict during expiration, isolating areas of residual high pressure and thus limiting gas exchange [ 209 ]. Appropriate MV settings, especially PEEP, for patients with EFL can be very different than typical care; improved modelling could aid detection and PEEP titration to deliver appropriate patient-specific care [ 209 ].…”
Section: The Path Forward For Mechanical Ventilation and The Role Of mentioning
confidence: 99%
“…Expiratory flow limitation (EFL) is believed to occur when smaller airways constrict during expiration, isolating areas of residual high pressure and thus limiting gas exchange [ 209 ]. Appropriate MV settings, especially PEEP, for patients with EFL can be very different than typical care; improved modelling could aid detection and PEEP titration to deliver appropriate patient-specific care [ 209 ]. MV intended to be protective can negatively affect hemodynamics in ARDS patients [ 1 ].…”
Section: The Path Forward For Mechanical Ventilation and The Role Of mentioning
confidence: 99%